2014
DOI: 10.3892/or.2014.2965
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol induces cell cycle arrest and apoptosis in renal cell carcinoma through EGFR/p38 signaling

Abstract: Kaempferol has been shown to inhibit cell growth, induce apoptosis and cell cycle arrest in several tumors, but not in renal cell carcinoma (RCC). In the present study, we investigated the effects of kaempferol and the underlying mechanism(s) on the cell growth of RCC cells. MTT assay and colony formation assay were used to study cell growth, and flow cytometry was used to study apoptosis and cell cycles in different RCC cells treated with various doses of kaempferol. A significant inhibition on cell growth, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…Kaempferol also inhibited the colony formation ability and promoted apoptosis in CCA cells, which were consistent with the cell viability variation. Previous studies have reported that kaempferol induces apoptosis by regulating Bcl-2 and caspase family proteins [15][16][17]30]. Our results showed that kaempferol did not affect the expression of Bcl-xL or survivin, but it significantly reduced the expression of Bcl-2 and increased the expression of Bax.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Kaempferol also inhibited the colony formation ability and promoted apoptosis in CCA cells, which were consistent with the cell viability variation. Previous studies have reported that kaempferol induces apoptosis by regulating Bcl-2 and caspase family proteins [15][16][17]30]. Our results showed that kaempferol did not affect the expression of Bcl-xL or survivin, but it significantly reduced the expression of Bcl-2 and increased the expression of Bax.…”
Section: Discussionsupporting
confidence: 60%
“…Epidemiological studies have confirmed that kaempferol reduces the risk of developing cancer in smokers [12][13][14]. It also exhibits antitumor activity in various cancers, including renal cell carcinoma, breast cancer, gastric cancer, hepatocellular carcinoma, colon cancer, and CCA [15][16][17][18][19][20]. Lee et al [21] have reported that kaempferol competes with ATP in binding to PI3K in mouse epidermal JB6 P + cells and subsequently inhibits the downstream activity of AKT and its transcription factor targets [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vitro and in vivo studies have shown the antiproliferative and proapoptotic activities of KMF against various types of cancers including breast (Azevedo et al, 2015;Kim, Hwang, & Choi, 2016;Liao et al, 2016), ovarian (Luo, Rankin, Li, Depriest, & Chen, 2011), lung (Kuo et al, 2015), pancreas (Zhang, Chen, Li, Chen, & Yao, 2008), esophagus (Yao et al, 2016), stomach , colon , prostate (Halimah et al, 2015), bladder (Dang et al, 2015), kidney (Song et al, 2014) and others. Most of these studies demonstrate that the mechanism of KMF is dependent on the inhibition of proliferation of various cancer cells either via cell cycle arrest or induction of apoptosis (Kuo et al, 2015;Liao et al, 2016).…”
Section: Cell Cycle Arrest and Apoptosis By Kaempferolmentioning
confidence: 99%
“…including G0/G1 transition in esophagus squamous cell carcinoma (Yao et al, 2016) or G2/M transition in HT-29 human colon cancer cells . KMF additionally inhibits the expression of various cyclins like cyclin D1 and cyclin E in breast cancer cells (Kim et al, 2016), cyclin B1 in gastric cancer cells and renal cell carcinoma (Song et al, 2014 cyclin D, cyclin E and cyclin A in colon cancer cells and cyclin-dependent kinases like CDK4 and CDK2 . KMF treatment has also been known to up-regulate the CDK inhibitors including p21 and p27 ( Fig.…”
Section: Cell Cycle Arrest and Apoptosis By Kaempferolmentioning
confidence: 99%
“…Choi and Ahn (2008[15]) reported kaempferol as potential inducer of apoptosis via G2/M cell cycle arrest in MDA-MB-453. Song et al (2014[76]) reported that kaempferol effectively inhibited EGFR/p38 signaling activation, reduced cyclin B1 expression and increased p21 expression along with PARP cleavage and induced apoptosis in human renal carcinoma (786-O and 769-P) cells. Lee et al (2015[56]) reported that quercetin induced apoptosis through mitochondrial pathways by ROS mediated ERK activation in HL-60 cells.…”
Section: Discussionmentioning
confidence: 99%